Lupus acute cardiomyopathy is highly responsive to intravenous immunoglobulin treatment: Case series and literature review. Issue 18 (7th May 2021) - Meridor, Katya; Shoenfeld, Yehuda; Tayer-Shifman, Oshrat; Levy, Yair
Abstract: Introduction: Intravenous immunoglobulin (IVIg) is currently used with considerable success for the treatment of many autoimmune diseases, including systemic lupus erythematosus (SLE). Among its various indications, IVIg has also been found to be beneficial in myocarditis, whether or not it is associated with an autoimmune disease. Nevertheless, data regarding IVIg treatment for myocarditis/cardiomyopathy in patients with SLE are sparse. The objective of this case series was to describe our experience with IVIg as a treatment for lupus myocarditis and to review the literature for IVIg for this indication. Patient concerns: We report 5 female patients with SLE, who presented with signs of acute heart failure including pulmonary congestion and arrhythmias. Diagnosis: Echocardiography demonstrated new reduced left ventricular ejection fraction of 20% to 30%. Two patients underwent coronary artery angiography, which demonstrated normal coronary arteries, supporting the diagnosis of myocarditis or nonischemic cardiomyopathy. Interventions: High-dose IVIg treatment was initiated in all 5 patients. Outcomes: Following the treatment, clinical and echocardiographic improvement in cardiac function occurred within a few days to 1 month. This dramatic improvement persisted for several years. Conclusion: Based on our case series, we believe that IVIg has an important role in the management of lupus acute cardiomyopathy. This safe, well-tolerated optional treatment should be considered, especially in severe cases.